2020
DOI: 10.1093/femsec/fiaa163
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community assembly in Atlantic cod larvae (Gadus morhua): contributions of ecological processes and metacommunity structure

Abstract: Many studies demonstrate the importance of the commensal microbiomes to animal health and development. However, the initial community assembly process is poorly understood. It is unclear to what extent the hosts select for their commensal microbiota, whether stochastic processes contribute, and how environmental conditions affect the community assembly. We investigated community assembly in Atlantic cod larvae exposed to distinct microbial metacommunities. We aimed at quantifying ecological processes influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…The Phusion buffer HF, 0.015 units/µL of Phusion Hot Start II DNA polymerase, 1 µL of DNA template and dH20 to a total volume of 25 µL. The amplicon library was prepared as described previously (30). In brief, we used the SequalPrep Normalisation plate (96) kit (Invitrogen) to normalise and purify PCR products and the Illumina Nextera XT Index kits (FC-131-2001 andFC-131-2004) for amplicon indexing.…”
Section: Experimental Design and Sampling Schemementioning
confidence: 99%
“…The Phusion buffer HF, 0.015 units/µL of Phusion Hot Start II DNA polymerase, 1 µL of DNA template and dH20 to a total volume of 25 µL. The amplicon library was prepared as described previously (30). In brief, we used the SequalPrep Normalisation plate (96) kit (Invitrogen) to normalise and purify PCR products and the Illumina Nextera XT Index kits (FC-131-2001 andFC-131-2004) for amplicon indexing.…”
Section: Experimental Design and Sampling Schemementioning
confidence: 99%
“…However, host pressures in the juvenile or adult cod gut are not widely described, a study design similar to the zebrafish study but with Atlantic cod could help elucidate these factors. Research on the Atlantic cod larval phase has suggested that selective pressures in the gut, associated with host intestinal development combined with stochastic pressures, shaped the gut microbiota 47,48 . Ecological theory has been loosely applied to manipulate the microbiome of Atlantic cod larvae by changing the tank water to improve survival rates using selection 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The amplicon library preparation and processing of the Illumina sequencing data was performed as described by Vestrum et al [28]. In short, for the first stage of amplification, the reactions were run for 38 cycles for water samples and 40 cycles for cod larval samples (98 • C 15 s, 55 • C 20 s, 72 • C 20 s), with 0.3 µM of each primer, 0.25 mM of each dNTP, 2 mM of MgCl 2 , 12 µM of BSA, glycerol (10%), Phusion Hot Start II High-Fidelity DNA Polymerase and reaction buffer from Thermo Scientific in a total volume of 20 µL.…”
Section: Characterisation Of Microbial Communitiesmentioning
confidence: 99%